Study of new particle formation events in southern Italy. (1st January 2021) - Dinoi, A.; Weinhold, K.; Wiedensohler, A.; Contini, D.
Abstract: New particle formation (NPF) events were studied in the urban background of Lecce (Italy) at the ECO Environmental-Climate Observatory, GAW/ACTRIS regional station. The objective of this study was to obtain long-term information on nucleation phenomenon in the Salentum peninsula, a coastal area of the central Mediterranean basin for which no extensive data exists. Particle number size distributions of the atmospheric aerosol were continuously collected by a Mobility Particle Size Spectrometer (MPSS) in the size range of 10–800 nm. For this investigation, data was analyzed for the period from January 2015 to July 2016 together with simultaneous measurements of gaseous pollutants (SO2, NO, NO2, and O3 ) and meteorological parameters. Throughout the observation period, nucleation events have been identified in approximately 21% of days. The classification of the events showed a seasonal trend with higher frequencies in warm seasons with a maximum in September (38%) while the highest non-event days fraction was observed in cold seasons, 90% in November and December. The fraction of undefined days peaked in August and September, 15 and 19% respectively. The analysis of reactive gas showed that NO, NO2, and O3 did not play an evident role in the formation process, as observed by the comparison between event and non-event monthly median concentrations. N ucleation phenomenon seemed instead to be very sensitive to SO2 that was present with higher (about 40%) monthly median concentrations during event days compared to non-event days. The condensation sink (CS), calculated for the complete observational period, showed similar values comparing event and non-event days. It is noteworthy that all the events occurred during the central hours of the day, high pressure, dry air (RH<55%) and without significant cloud cover. The event days were characterized by winds originating predominately from the north and northwest directions, as shown by the analysis of the back-trajectories . Graphical abstract: Image 1 Highlights: New particle formation shows a trend with higher frequencies in warm seasons. All events occurred with no cloud cover, high pressure, and dry air (RH<55%). NO, NO2, and O3 did not play an evident role in the formation process. SO2 concentrations were on average 40% higher during days with nucleation events. Event days were associated to air masses circulating from inland (N-NW).